Factors Influencing Plasma Concentrations of Valproic Acid in Pediatric Patients With Epilepsy and the Clinical Significance of CYP2C9 Genotypes in Personalized Valproic Acid Therapy - Ma, Bingsuo; Yang, Kun; Li, Xinping; Su, Ning; Yu, Ting; Zou, Yan; Xu, Xingmeng; Wang, Fei; Cheng, Jingdong; Yan, Zijun; Chen, Tong; Zhang, Liangming (Therapeutic drug monitoring, 2024)
The aim of this study was to investigate the factors affecting plasma valproic acid (VPA) concentration in pediatric patients with epilepsy and the clinical significance of CYP2C9 gene polymorphisms in personalized dosing using therapeutic drug monitoring and pharmacogenetic testing. The medical records of children with epilepsy who underwent therapeutic drug monitoring at our institution between July 2022 and July 2023 and met the inclusion criteria were reviewed. Statistical analysis was performed to determine whether age, sex, blood ammonia, liver function, kidney function, and other characteristics affected the concentration-to-dose ratio of VPA (CDRV) in these patients. To investigate the effect of CYP2C9 polymorphisms on CDRV, DNA samples were collected from patients and the CYP2C9 genotypes were identified using real-time quantitative PCR. The mean age of 208 pediatric patients with epilepsy was 5.50 ± 3.50 years. Among these patients, 182 had the CYP2C9 *1/*1 genotype, with a mean CDRV (mcg.kg/mL.mg) of 2.64 ± 1.46, 24 had the CYP2C9 *1/*3 genotype, with a mean CDRV of 3.28 ± 1.74, and 2 had the CYP2C9 *3/*3 genotype, with a mean CDRV of 6.46 ± 3.33. There were statistical differences among these 3 genotypes ( P < 0.05). The CDRV in these patients were significantly influenced by age, aspartate aminotransferase, total bilirubin, direct bilirubin, globulin, albumin/globulin ratio, prealbumin, creatinine, and CYP2C9 polymorphisms. In addition, multivariate linear regression analysis identified total bilirubin, direct bilirubin, and CYP2C9 polymorphisms as independent risk factors for high CDRV. Liver problems and mutations in the CYP2C9 gene increase VPA levels. This underscores the importance of considering these factors when prescribing VPA to children with epilepsy, thereby enhancing the safety and efficacy of the therapy.